Percutaneous closure of patent ductus arteriosus in children: Immediate and short-term changes in left ventricular systolic and diastolic function - Saurabh Kumar Gupta; K M Krishnamoorthy; Jaganmohan A Tharakan; S Sivasankaran; G Sanjay; S Bijulal; T Anees (Wolters Kluwer Medknow Publications, 2011)
Objective: To evaluate the effect of percutaneous closure of patent ductus arteriosus (PDA) on left ventricular (LV) systolic and diastolic function in children. Background: Limited studies are available on alteration in LV hemodynamics, especially diastolic function, after PDA closure. Methods: Thirty-two consecutive children with isolated PDA treated by trans-catheter closure were studied. The LV systolic and diastolic function were assessed by two-dimensional (2D) echocardiography and tissue Doppler imaging 1 day before the PDA closure, on day 1, and on follow-up. Results: At baseline, none of the patients had LV systolic dysfunction. On day 1 post-PDA closure, 8 (25%) children developed LV systolic dysfunction. The baseline LV ejection fraction (LVEF), LV end-systolic dimension (LVESD), and PDA diastolic gradient predicted the post-closure LVEF. Patients who developed post-closure LV systolic dysfunction had poorer LV diastolic function than those who did not. LV diastolic properties improved after PDA closure; however, the improvement in LV diastolic properties lagged behind the improvement in the LV systolic function. All children were asymptomatic and had normal LVEF on follow up of >3 months. Conclusions: Percutaneous closure of PDA is associated with the reversible LV systolic dysfunction. Improvement in the LV diastolic function lags behind that in the LV systolic function.